Parental education level on the development of children's oral hygiene skills (One Health & Risk Management, 2024)
Introduction. Dental caries is a significant public health issue due to its high incidence among the population. While modern scientific research highlights effective treatments for this condition, prevention remains crucial, directly impacting health and quality of life, especially when early preventive habits are instilled. This study aims to explore how parents' educational levels and other factors influence the acquisition, use, and proper application of oral hygiene knowledge among primary school children.Material and methods. The study surveyed 678 parents of primary school children across 9 administrative regions, including both urban and rural areas of the Republic of Moldova. It employed a randomized approach, involving respondents from all social groups.Results. This study found that parental education level is a crucial factor influencing the proper development of oral hygiene skills, which can prevent dental conditions. Higher parental education was positively associated with urban living environment and family income. Additionally, well-educated parents tend to visit dentists more regularly, which also reflects in better oral hygiene practices at home for their children.Conclusions. Children's oral hygiene habits are strongly shaped by socioeconomic factors and the care parents show. Increasing parental education levels, whether in urban or rural settings, plays a pivotal role in fostering correct dental hygiene practices early in life, thereby ensuring long-term oral health habits into adulthood.